Scientific aspects of women's gymnastics - Sands, W. A.; Caine, D. J.; Borms, J. (Medicine and Sport Science, 2003)
1 Introduction 8 Biomechanics 46 Injury and Growth 72 Injury Epidemiology 110 Kinanthropometry 128 Physiology 162 Conclusion 171 Subject Index